Pengaruh Tingkat Kemandirian Fiskal Daerah, DAK, dan Belanja Modal terhadap Kemiskinan di Jawa Tengah - Rahmawati, Rizka Nur; Pratiwi, Hesti Eka; Lisniwati, Mila; Afriani, Lutfiah Dwi; Haryadi, Akbar Kharisma (Direktorat Sistem Perbendaharaan, 2024)
Central Java Province has the second highest poverty rate in the nation, second only to the Special Region of Yogyakarta. This research aims to determine the influence of regional fiscal independence, the Special Allocation Fund (DAK), and regional capital expenditures toward poverty in Central Java Province. This study employs a quantitative approach, utilizing a fixed-effects panel data model. The panel data were obtained by combining time-series data for 2017-2022 and cross-section data from 35 regencies and cities in Central Java. The results showed that all independent variables had a simultaneous effect on poverty. Notably, the level of regional fiscal independence has a positive effect, while DAK has a negative effect. Furthermore, the study also found that regional capital expenditure exhibits a positive correlation with poverty.